?COMPARISON BETWEEN Two DETECTION TECHNIQUES OF SEED-BoRNE PATHOGENS IN CUCURBITS IN BANGLADESH - Begumv, Hosne A; Momin, A (Biological Sciences - PJSIR, 2000)
Fifty four seed samples of three cucurbits namely sweet gourd (Cucurbita moschata Duch. Ex Poir.), white gourd (Benincasa hispida Cogn.) andbitter gourd (Momordica charantia L.) werecollected from sixdifferent districts of Bangladesh, to find out asuitabledetectiontechniqueofassociatedseed-bornefungiinlaboratoryconditions. Threedifferentdetectionmethodsnamely, dry inspection, blotter test and seedling symptom test were compared in present study. Among the tested three detection techniques, moreinfection rateswereobserved forAspergillus flavus andPenicillium inallcucurbitseedsinblottertest method, whereas higher infection caused by Fusarium and Rhizopus were recorded in test tube seedling symptom test. The higher germination percentage of cucurbit seedswas observed inblotter testand itis lessexpensive, quick anduseful for the detection of most of the infectious fungi.